Characterization of Spirometra erinaceieuropaei Plerocercoid Cysteine Protease and Potential Application for Serodiagnosis of Sparganosis. - Li Na Liu; Zhong Quan Wang; Xi Zhang; Peng Jiang; Xin Qi; Ruo Dan Liu; Zi Fang Zhang; Jing Cui (Public Library of Science (PLoS), 2015)
BACKGROUND:Sparganosis is a neglected but important food-borne parasitic zoonosis. Clinical diagnosis of sparganosis is difficult because there are no specific manifestations. ELISA using plerocercoid crude or excretory-secretory (ES) antigens has high sensitivity but has cross-reactions with other helminthiases. The aim of this study was to characterize Spirometra erinaceieuropaei cysteine protease (SeCP) and to evaluate its potential application for serodiagnosis of sparganosis. METHODOLOGY/PRINCIPAL FINDINGS:The full length SeCP gene was cloned, and recombinant SeCP (rSeCP) was expressed and purified. Western blotting showed that rSeCP was recognized by the serum of sparganum-infected mice, and anti-rSeCP serum recognized the native SeCP protein of plerocercoid crude or ES antigens. Expression of SeCP was observed at plerocercoid stages but not at the adult and egg stages. Immunolocalization identified SeCP in plerocercoid tegument and parenchymal tissue. The rSeCP had CP activity, and the optimum pH and temperature were 5.5 and 37°C, respectively. Enzymatic activity was significantly inhibited by E-64. rSeCP functions to degrade different proteins and the function was inhibited by anti-rSeCP serum and E-64. Immunization of mice with rSeCP induced Th2-predominant immune responses and anti-rSeCP antibodies had the potential capabilities to kill plerocercoids in an ADCC assay. The sensitivity of rSeCP-ELISA and ES antigen ELISA was 100% when performed on sera of patients with sparganosis. The specificity of rSeCP-ELISA and ES antigen ELISA was 98.22% (166/169) and 87.57% (148/169), respectively (P<0.05). CONCLUSIONS:The rSeCP had the CP enzymatic activity and SeCP seems to be important for the survival of plerocercoids in host. The rSeCP is a potential diagnostic antigen for sparganosis.